Wharton's Jelly Mesenchymal Stromal Cells from Human Umbilical Cord: a Close-up on Immunomodulatory Molecules Featured In Situ and In Vitro - Corsello, Tiziana; Amico, Giandomenico; Corrao, Simona; Anzalone, Rita; Timoneri, Francesca; Lo Iacono, Melania; Russo, Eleonora; Spatola, Giovanni Francesco; Uzzo, Maria Laura; Giuffrè, Mario; Caprnda, Martin; Kubatka, Peter; et al. (Stem cell reviews and reports, 2019)
Therapeutic options for end-stage organ failure are often limited to whole organ transplantation. The tolerance or rejection of the transplanted organ is driven by both early non-specific innate and specific adaptive responses. The use of mesenchymal stromal cells (MSCs) is considered a promising tool in regenerative medicine. Human umbilical cord (HUC) is an easily available source of MSCs, without relevant ethical issues. Moreover, Wharton's jelly-derived MSCs (WJ-MSCs), showed consistent immunomodulatory features that may be useful to promote immune tolerance in the host after transplantation. Few data are available on the phenotype of WJ-MSCs in situ. We investigated the expression of immune-related molecules, such as HLAs, IDO, CD276/B7-H3, and others, both in situ (HUC) and in in vitro-cultured WJ-MSCs. Morphological and biochemical techniques were used to define the expression of such molecules. In addition, we focused on the possible role of CD276/B7-H3 on T cells proliferation inhibition. We assessed CD276/B7-H3 expression by WJ-MSCs both in situ and alongside cell culture. WJ-MSCs were able to suppress T cell proliferation in mixed lymphocyte reaction (MLR). Moreover, we describe for the first time a specific role for CD276/B7-H3, since the immunomodulatory ability of WJ-MSCs was abolished upon anti-CD276/B7-H3 antibody addition to the MLR. These results further detail the immune regulation properties and tolerance induction exerted by human WJ-MSCs, in particular pointing to CD276/B7-H3 as one of the main involved factors. These data further suggest WJ-MSCs as potent tools to modulate local immune response in "support-type" regenerative medicine approaches.
Keywords: pupečník; kultivované buňky; In Vitro Techniques; Cell Differentiation; Umbilical Cord; CD276; Whartonův rosol; cytokiny; Wharton Jelly; Regenerative medicine; Stem cells; Cell Proliferation; Cytokines; techniky in vitro; Mesenchymal Stem Cells; Immunomodulation; Human umbilical cord; B7 Antigens; antigeny B7; mezenchymální kmenové buňky; Cells, Cultured; aktivace lymfocytů; B7-H3; Humans; Lymphocyte Activation; Wharton’s jelly mesenchymal stromal cells; proliferace buněk; Cell therapy; buněčná diferenciace; Lymphocyte inhibition; lidé